Democratizing the Common Agricultural Policy in Portugal: The Case of the “Civic Coalition Participar no pepac”. - Viegas, Miguel (2025)
The Common Agricultural Policy (cap) accounts for one third of the European Union’s budget. For Portugal, it totals a financial envelope of 10 billion euros for the period 2021-2027. Despite this being a considerable sum of resources, the debate on the cap never aroused great interest on the part of the public. Over the last few decades, the discussion on the application of cap funds has been monopolized by farmers’ associations, which are at the same time its most direct beneficiaries. In Portugal, the creation of the Civic Coalition Participate in pepac represents the first relevant experience in broadening the discussion of agricultural policy in Portugal. This article, based on this unprecedented experience in Portugal, characterizes the current process of building and implementing the cap in Portugal, criticizes the narrow limits of its public participation and points to a set of recommendations aimed at greater involvement of society in a public policy with strong implications in the economic, social and environmental fields.